Respuesta :
Answer:
The value of x is -2.
Step-by-step explanation:
First, you have to eliminate the brackets by expanding :
[tex]2(x - 4) = 4(2x + 1)[/tex]
[tex]2x - 8 = 8x + 4[/tex]
Next, you have to move all the like-terms to one side :
[tex]2x - 8 - 8x = 4[/tex]
[tex] - 6x = 4 + 8[/tex]
[tex] - 6x = 12[/tex]
[tex]x = 12 \div ( - 6)[/tex]
[tex]x = - 2[/tex]
Answer:
[tex]x = - 2[/tex]
Step-by-step explanation:
[tex]2(x - 4) = 4(2x + 1) \\ 2x - 8 = 8x + 4 \\ 2x - 8x = 8 + 4 \\ - 6x = 12 \\ \frac{ - 6x}{ - 6} = \frac{12}{ - 6} \\ x = - 2[/tex]
hope this helps
brainliest appreciated
good luck! have a nice day!